PENGARUH NAA DAN BAP TERHADAP PERTUMBUHAN EMBRIOSOMATIK PISANG CAVENDISH (Musa acuminata L.) FASE GLOBULAR SECARA IN VITRO - Silvina, Fetmi; Nurbaiti, Nurbaiti; Rahmita, Nurfa (Fakultas Pertanian, Universitas Janabadra, 2024)
Cavendish banana is a type of commercial banana that has a high nutritional content and complete. The problem of providing cavendish banana seeds in large quantities is very difficult, because cavendish bananas only produce 2 – 3 offspring from one parent, alternative solution for providing seeds in large quantities can be done in vitro. This research aims to determine the interaction effect of NAA and BAP, NAA factor and BAP factor and obtain the best treatments for the growth of embryosomatic explants of cavendish banana globular phase. This research was conducted using a random design of factorial with two factors: NAA (0; 1; 2; 3) ppm and BAP (0: 1,5; 3; 4,5) ppm. Parameters observed were shoots amergence, number of shoots, shoot height, number of roots, root length, and the percentage of successful shoot formation. The data were analyzed using analysis of variance and followed by Duncan double distance at 5% level. The results showed that the interaction of NAA and BAP administration affect the parameters were shoots amergence, number of shoots, shoot height, number of roots and root length with the best treatment was 2 ppm NAA and 3 ppm BAP. Application of NAA significantly affected the time of bud amergence, number of shoots, shoot height, number of roots and root length with the best treatment was 2 ppm NAA. Application of BAP significantly affected the time of bud amergence, number of shoots, shoot height, number of roots and root length with the best treatment was 3 ppm BAP. The percentage of successful shoot formation range from 77,80 – 100%.